2020
DOI: 10.22490/21456453.3849
|View full text |Cite
|
Sign up to set email alerts
|

Biosurfactants produced by metal-resistant Pseudomonas aeruginosa isolated from Zea mays rhizosphere and compost

Abstract: Contextualization: Pseudomonas aeruginosa is capable of producing biosurfactants which have many uses in bioremediation and the production of antiviral, antibacterial, antiparasitic, sporicidal and antifungal agents, among others.   Knowledge gap: This study describes the production of mono and di-rhamnolipid biosurfactants by P. aeruginosa strains isolated from Zea mays rhizosphere and composts in the state of Guerrero, Mexico.  Purpose: The overall aims were to investigate biosurfactant, pyocyani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…was studied. The biosurfactant produced by the bacterial isolates exhibited antibacterial and antifungal activity, with similar results to that reported by Matei et al ( 2017 ) and Aguirre-Noyola et al ( 2020 ). They found that the extracted biosurfactants exhibited antibacterial and antifungal activities.…”
Section: Discussionsupporting
confidence: 89%
“…was studied. The biosurfactant produced by the bacterial isolates exhibited antibacterial and antifungal activity, with similar results to that reported by Matei et al ( 2017 ) and Aguirre-Noyola et al ( 2020 ). They found that the extracted biosurfactants exhibited antibacterial and antifungal activities.…”
Section: Discussionsupporting
confidence: 89%